pH sensor using Langmuir-Blodgett overlays on polished optical fibers - Flannery, D.; James, Stephen W.; Tatam, Ralph P.; Ashwell, Geoffrey J. (Optical Society of America, 1997)
Evanescent coupling between a side-polished single-mode optical fiber and a single-mode, pH-sensitive Langmuir-Blodgett overlay is used to demonstrate an intrinsic fiber-optic pH sensor. The sensor shows a wavelength sensitivity of 18.8 ± 0.8 nm/pH and a transmission sensitivity of 9.7 ± 0.8 dB/pH when operating at 750 n